2022
DOI: 10.1002/pon.5946
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress of cancer patients caused by treatment delay during the COVID‐19 pandemic in China: A cross‐sectional study

Abstract: Objective The currents study sought to explore the impact of treatment delay on the mental health for patients with cancer during the 2019 coronavirus disease (COVID‐19) pandemic. Methods Travel restrictions were imposed in most areas of the country between 23 January 2020 and 25 February 2020 owing to the COVID‐19 epidemic. Travel restrictions were lifted from 26 February 2020 to 12 March 2020. The number of new confirmed cases significantly reduced after 12 March 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The observed association between delayed and unmet access to prescription drugs and increased anxiety-related issues corresponds with the wider interruptions in healthcare access and anxiety linked to COVID-19. 26 , 27 , 28 The factors responsible for the association between delayed and unmet access to prescription drugs and increased anxiety-related symptoms are likely varied. People may have faced compounded issues, particularly in managing the unpredictability of an international health emergency while grappling with disruptions in pharmacological schedules.…”
Section: Discussionmentioning
confidence: 99%
“…The observed association between delayed and unmet access to prescription drugs and increased anxiety-related issues corresponds with the wider interruptions in healthcare access and anxiety linked to COVID-19. 26 , 27 , 28 The factors responsible for the association between delayed and unmet access to prescription drugs and increased anxiety-related symptoms are likely varied. People may have faced compounded issues, particularly in managing the unpredictability of an international health emergency while grappling with disruptions in pharmacological schedules.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed treatment lead to progression of the disease and raised the mortality rate. A study done by Yingjun ye et al found that psychological distress was significantly higher in the patient with cancer during COVID 19 as compared to the healthy volunteers [11].…”
Section: Cancer Managementmentioning
confidence: 96%
“…This suggests that the consequences for cancer patients, when faced with the dual challenge of seeking timely diagnosis and navigating the pandemic, can be profound and deeply distressing. [52,53] This could be a contributing factor to the lower comment scores of cancer hospitals during the pandemic.…”
Section: Difference Between Children's Hospital Maternity Hospital An...mentioning
confidence: 99%